IMPACT OF PRODUCT QUALITY ON LEVEL OF CUSTOMER SATISFACTION IN SLEEPOLIC BANDUNG E-COMMERCE - Neng Wulandari; Tiris Sudrartono (Journal of Management Small and Medium Enterprises (SMEs), 2026)
The objective of this study is to evaluate the effect of product quality on customer satisfaction at Sleepolic e-commerce platform in Bandung and to identify potential strategies for improving customer satisfaction. A descriptive quantitative approach was employed, with data collected through questionnaires distributed to 33 respondents. Data analysis was conducted using simple linear regression with the assistance of SPSS version 30. The analytical procedures included validity testing, t-testing, and coefficient of determination analysis. The findings suggest that higher product quality leads to a positive and significant increase in customer satisfaction. The coefficient of determination indicates that product quality explains 69.9% of the variance in customer satisfaction, while the remaining proportion is attributable to other factors not examined in this study. Based on these findings, it is recommended that Sleepolic enhance its marketing efforts by offering discounts, promotional programs, and customer loyalty initiatives to further improve customer satisfaction and attract a broader customer base. Keywords: Product Quality; Customer Satisfaction; E-commerce